2020
DOI: 10.1177/0890117120971121
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Susceptibility to E-Cigarettes: An Update From the 2018 National Youth Tobacco Survey

Abstract: Purpose: Examine correlates of e-cigarette susceptibility among adolescents. Design: Secondary data analyses using the 2018 National Youth Tobacco Survey, excluding participants under 12 and over 17. Setting: United States middle and high schools. Subjects: Never e-cigarette users ( n = 12,439) ages 12-17. Measures: Relationships between e-cigarette susceptibility and age, sex, race/ethnicity, ever tobacco use, perceived ease of purchasing tobacco products, perceived harm, relative addictiveness, household use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
1
16
3
Order By: Relevance
“…The Pierce measure ( Pierce et al, 1996 ) was initially developed to forecast cigarette smoking but has been adapted in various forms to predict initiation of ENDS ( Strong et al, 2015 , Bold et al, 2017 , Cheng et al, 2021 ). In this study we account for this measure of susceptibility and other variables associated with likelihood of ENDS initiation and sleep quality, including parental education ( Vu et al, 2020 ), household income ( Patel et al, (2021 ), availability of tobacco products in the home ( Bailey et al, 2022 ; ( Bouchard et al, 2018 ), prior use of tobacco, alcohol, and illicit substances ( Brake, 2019 ), school performance ( Nicksic and Barnes, 2019 ), experiences with anxiety and depression ( Green et al, 2018 , Jamieson et al, 2020 ), perceptions of ENDs harmfulness ( Tackett et al, 2021 , Strong et al, 2019 ), sensation seeking ( Case et al, 2017 , Carey et al, 2019 ), having friends that use ENDS ( Groom et al, 2021 ), exposure to ENDS promotions on social media ( Holtz et al, 2021 ), Body Mass Index (BMI) ( Moore et al, 2011 ) and physical activity ( Youngstedt, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Pierce measure ( Pierce et al, 1996 ) was initially developed to forecast cigarette smoking but has been adapted in various forms to predict initiation of ENDS ( Strong et al, 2015 , Bold et al, 2017 , Cheng et al, 2021 ). In this study we account for this measure of susceptibility and other variables associated with likelihood of ENDS initiation and sleep quality, including parental education ( Vu et al, 2020 ), household income ( Patel et al, (2021 ), availability of tobacco products in the home ( Bailey et al, 2022 ; ( Bouchard et al, 2018 ), prior use of tobacco, alcohol, and illicit substances ( Brake, 2019 ), school performance ( Nicksic and Barnes, 2019 ), experiences with anxiety and depression ( Green et al, 2018 , Jamieson et al, 2020 ), perceptions of ENDs harmfulness ( Tackett et al, 2021 , Strong et al, 2019 ), sensation seeking ( Case et al, 2017 , Carey et al, 2019 ), having friends that use ENDS ( Groom et al, 2021 ), exposure to ENDS promotions on social media ( Holtz et al, 2021 ), Body Mass Index (BMI) ( Moore et al, 2011 ) and physical activity ( Youngstedt, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although several studies included susceptibility to e-cigarette use, they are limited in that they did not include multi-faceted covariates in the exploration of risk factors [21]. For instance, Tackett [22], Copp [23], Gottschlich [24], and Williams [25] investigated youth e-cigarette use susceptibility in the USA, Canada, and Guatemala, respectively. They included individual factors such as demographics, and perceptions of smoking and substance use, but did not include psychological and personality factors that were also signi cant predictors of youth e-cigarette use.…”
Section: Introductionmentioning
confidence: 99%
“…Susceptibility to tobacco use is measured among those who have not yet used a tobacco product, and is defined as a lack of a firm decision not to use a particular tobacco product. [10][11][12][13][14] While most research on this construct has focused on youth (i.e., 12-to 17-yearolds), 12,[15][16][17][18][19][20][21][22][23] recent research demonstrates it is relevant to young adults, too. Previous research on tobacco product susceptibility has indicated that susceptibility varies by specific tobacco products and age in young adults.…”
Section: Introductionmentioning
confidence: 99%
“…24 A convenience sample of college students in Upstate New York in 2013 found that among 18, 19, and 20 to 23-year-olds, the prevalence of susceptibility to e-cigarette use was 39.5%, 40.8%, and 36.8%, respectively. 25 A different 2014-2015 nationally representative study of adolescents and young adults (ages [13][14][15][16][17][18][19][20][21][22][23][24][25] found that among never users of hookah and little cigars/ cigarillos (LCCs), 17.7% and 14.8% were susceptible to use, respectively. 26 In 2016-2017, a study surveying college freshmen at a large university found that 30.0% of those who reported they were non-susceptible to hookah use at baseline reported onset of susceptibility to hookah use by the end of the academic year.…”
Section: Introductionmentioning
confidence: 99%